2009
DOI: 10.1016/j.leaqua.2009.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Leadership and team cohesiveness across cultures

Abstract: a r t i c l e i n f o a b s t r a c tThis study examines the relation between leadership and team cohesiveness in different societal cultures. We expect direct effects of societal culture on leadership and team cohesiveness, as well as a moderating effect of culture on the relationship between leadership and cohesiveness. Data were collected from 29,868 managers and 138,270 corresponding team members in 80 countries. Multilevel analysis was used to test the hypotheses, relating societal individualism-collectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
115
0
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 170 publications
(124 citation statements)
references
References 52 publications
(39 reference statements)
6
115
0
3
Order By: Relevance
“…Where power distance is high, leaders tend to be less participative and more authoritarian and directive. A recent study by Wendt et al (2009) showed that managers from 80 countries, including Iran, prefer to use supportive behavior relatively more than directive behavior, and thereby foster team cohesion.…”
Section: Iranmentioning
confidence: 99%
“…Where power distance is high, leaders tend to be less participative and more authoritarian and directive. A recent study by Wendt et al (2009) showed that managers from 80 countries, including Iran, prefer to use supportive behavior relatively more than directive behavior, and thereby foster team cohesion.…”
Section: Iranmentioning
confidence: 99%
“…The only empirical study on the subject was conducted by Carson et al (2007), which focused on contextual antecedents of shared leadership in teams, such as shared purpose, social support, voice, and external team coaching, rather than the role of formal team leaders. Prior research has consistently shown that the leadership behavior of team leaders has a considerable impact on the attitudes of team members toward their jobs, team climate, and team performance (e.g., Barling, Weber, & Kelloway, 1996;Charbonneau, Barling, & Kelloway, 2001;Grojean, Resick, Dickson, & Smith, 2004;Howell & Avolio, 1993;Shamir, House, & Arthur, 1993;Taggar & Ellis, 2007;Wendt, Euwema, & van Emmerik, 2009;Wofford, Calabro, & Sims, 1975). Therefore, in this study, I attempt to investigate the role of the formal leader of the R&D team in developing shared leadership among team members.…”
mentioning
confidence: 99%
“…However, Hooijberg and Choi point out that while various researchers have examined the inherent differences between sectors, few have focused on whether management/leadership behavioural styles also vary. Various scholars from the contingency school claim that managerial/leadership effectiveness is contingent upon similarities between the national cultures of the managers/leaders and their followers (Brodbeck et al 2000;Wendt, Euwema, and van Emmerik 2009). The works of these scholars are grounded in prior categorizations of countries into clusters which are believed to share cultural attributes.…”
Section: Studies In Higher Educationmentioning
confidence: 99%